The Future of Allied Health leadership in New Zealand-Aotearoa: A literature review - Rebecca Kate George; Karen Webster (ACHSM, 2021)
Background: The allied heath, scientific and technical (allied health) workforce is the second largest workforce in New Zealand, providing diagnostic, therapeutic and preventative services. Increasingly consumers present with complex conditions requiring multiprofessional integrated services and a legacy of profession-focused leadership development is being challenged. [1] Future health and disability systems require leaders prepared to lead complex services, less focussed on their professional background and more on understanding their interprofessional services. [2, 3] The Allied health workforce is well placed to lead these systems, providing interprofessional experience, a biopsychosocial lens and collaborative models of practice. Aim: To provide an understanding of the literature and research available that addresses the leadership of healthcare services by allied health clinicians. Methodology: An initial database review was completed using a systematic approach, across CINAHL complete; EBSCO Business; Medline; and EBSCO Health databases from March 2020 to September 2020. An expanded search used Google Scholar and NZ, UK and Australian based government websites to access institutional documents, such as policies, reviews and reports. Results: The review identified an emerging pool of research on allied health leadership in Australia and the UK but a paucity of literature on allied health leadership in New Zealand. Three themes were identified and explored within the article: health leadership frameworks, current state and barriers and enablers identified. Conclusions: Literature advocates for a broader scope of clinicians into strategic leadership roles. Despite evidence of strategic allied health roles in New Zealand there remains a dearth of literature on allied health leadership. To foster and sustain the development of allied health leaders in New Zealand it is important to understand the enablers that impact this process.